Heurística Construtiva para o Problema de Orquestração da Coleta de Dados de Telemetria In-band - de Castro, Ariel Góes; Lorenzon, Arthur Francisco; Rossi, Fabio; Luizelli, Marcelo Caggiani (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2020)
With the increasing usage of networking services, network monitoring has become essential to assure quality of service. In-band Network Telemetry (INT) allows to embed network state information into probe packets. However, INT only defines primitives at device-level, while wide-scale monitoring remains undefined. In this paper, we propose an constructive algorithmic approach to determine the paths taken by probes collecting telemetry items. Results show that our approach generate solutions close to the optimal ones.